Inside Russia today - Gunther, John, 1901-1970 (London : Hamilton, 1958)
"Here, above all, is the new, post-Stalin Russia in which monolithic rigidity has been replaced by something mcuh more fluid, experimental, dynamic and, perhaps, more dangerous. Special emphasis is laid on the importance of the Sputnik and other Soviet advances in science, which, with developments in education, are documented and described with wealth of detail available in no other book." - publisher
1. Getting in -- 2. Moscow - size, shape, qualities -- 3. More about the third Rome -- 4. Some Soviet attitudes -- 5. The party circuit -- 6. Khrushchev at the top -- 7. More demi-gods and Thanes -- 8. A history of Russia in half an hour -- 9. The Soviet Union has fifteen Republics -- 10. Government and party -- 11. What's going on - de-Stalinization -- 12. Hungary and after -- 13. New worlds in science and education -- 14. Writers under Socialist Realism -- 15. Ballet, theatre, and entertainment -- 16. Some social patterns -- 17. Aspects of the economic picture -- 18. The Soviet armed forces -- 19. What has Russia got? -- 20. Leningrad and Kiev -- 21. Across the Black Sea to the Caucasus -- 22. Antique worlds of Central Asia -- 23. The Russians gamble for the world -- 24. Peace, co-existence, and the United States.
Includes bibliography and index.
HU OSA 300 - RFE/RL collection
Keywords: Soviet Union -- Politics and government